Teachers' Real and Perceived of ICTs Supported-Situation for Mathematics Teaching and Learning - Fathurrohman, Maman; Porter, Anne L; Worthy, Annette L (Universitas Ahmad Dahlan, 2017)
Purpose of this research was to gain information related to the real and perceived ICT Infrastructures, Facilities, and Resources in Bojonegara Sub District, Indonesia. This article emphasize the publication of this information because it is needed for implementation of technology-based mathematics teaching and learning. The method used was survey. Instruments of survey were questionnaires, unstructured interview guideline, and handycam. During the survey, total of 220 questionnaire packages were distributed to teachers, however only 119 (response rate 54.1%) of them were filled and returned. A total of 12 teachers were interviewed, with five of these interviews were video recorded. Several head masters welcomed and allowed researcher to visit their schools and make documentation of ICT Infrastructures, facilities, and resources, while the others did not allow the researcher to do that. Based on survey, many important findings have been discovered. It is suggested that the Teachers-Centered Learning with Technology is the most appropriate method of technology-based learning to be implemented.